Return to Warden's Grove : science, desire, and the lives of sparrows - Norment, Christopher (Sightline books., 2008)
Based on three seasons of field research in the Canadian Arctic, Christopher Norment's exquisitely crafted meditation on science and nature, wildness and civilization, is marked by bottomless prose, reflection on timeless questions, and keen observations of the world and our place in it. In an era increasingly marked by cutting-edge research at the cellular and molecular level, what is the role for scientists of sympathetic observation? What can patient waiting tell us about ourselves and our place in the world?